An Interpretive Systematic Review of a Researcher’s Contributions to EFL Reading Instruction: Themes, Methods, and Pedagogical Insights - Al-Jarf , Reima (Journal of English Language Teaching and Applied Linguistics, 2026)
This study sought to conduct an interpretive systematic review (ISR) of the authors’ research on EFL reading instruction published between 2001 and 2025. The ISR consists of twenty-seven studies categorized into 6 clusters: EFL reading material used, specialized reading texts and skills, reading combined with other skills, extensive reading, technology enhanced EFL reading instruction, and EFL reading assessment and material coverage. Across the corpus, the ISR shows that effective EFL reading instruction is multidimensional, authentic, strategically scaffolded, and enriched by technology and culturally responsive materials. The studies consistently demonstrate that learners progress most when instruction moves beyond the textbook and immerses them in real world genres, multimodal resources, and collaborative environments that mirror contemporary literacy practices. Authenticity was a recurring strength: exposure to genres such as inspirational quotes, linguistic landscapes, multicultural stories, mobile fiction apps, art texts, news headlines, advertisements, and legal documents expanded learners’ cultural awareness, strengthened inferential and critical reading skills, and prepared them to process specialized texts prior to translation tasks. Findings across clusters highlight several converging principles. Authentic materials enhance comprehension, technology increases engagement, explicit strategy instruction deepens processing, and extensive reading fosters autonomy and fluency. At the same time, the studies reveal persistent challenges, particularly with text structure, cohesive ties, genre specific features, and vocabulary inference, indicating the need for sustained, systematic instructional support. Structural issues also emerged, including limited textbook coverage and misalignment between curriculum and assessment, underscoring the importance of coherent program design and stronger teacher preparation. Technology enhanced studies showed that mobile e books, mind mapping software, online courses, synchronous web conferencing, reading apps, and online videos significantly improved comprehension, vocabulary, and engagement, especially for struggling readers. Assessment focused studies emphasized the need to align tests with instructional goals and learners’ linguistic and cognitive needs. The meta conclusion of this ISR is that EFL reading development is maximized when instruction is integrative, student centered, and responsive to learners’ linguistic, cognitive, and cultural needs, and when assessment and material coverage are aligned with these broader pedagogical aims. Overall, the ISR points toward a holistic, authentic, technology supported, and strategically scaffolded model of EFL reading instruction capable of meeting the complex demands of contemporary learners.